The Frequency of Extended Spectrum Beta Lactamase (ESBL) in Escherichia coli and Klebsiella pneumoniae: A Report from Mashhad, Iran - Fatemeh Ashrafian; Emran Askari; Elnaz Kalamatizade; MohammadJavad Ghabouli-Shahroodi; Mahboubeh Naderi-Nasab (Journal of Medical Bacteriology, 2015)
Background: In recent decades, extended spectrum beta-lactamase (ESBL) producing bacteria have increased worldwide. The most important causative agents of nosocomial infections throughout the world, Escherichia coli and Klebsiella pneumoniae as main ESBL-producing bacteria are so highly regarded. Trends  in  the  treatment  of  infections  by such  bacteria  have  led  to  a  global concern. This study was conducted to evaluate the incidence of ESBL producing E. coli and K. pneumoniae among inpatients and outpatients referred to the Imam Reza hospital unit in Mashhad during 2007-8. Methods: This study represents a descriptive cross-sectional study. All 339 samples from hospital and a special clinic of the Imam Reza hospital of Mashhad were collected and cultured in defined media. Identification by morphological and  biochemical  tests  were  performed  to  determine  the  Enterobacteriaceae genera. The secretion of ESBL was studied by the double disc diffusion method. At the end, the data were analyzed by statistical software. Results: Out of 339 isolates collected from 192 women (56.6%) and 147 men (43.4%), 26.5% of E. coli (n = 211) and 43% of K. pneumoniae (n = 128) were ESBL positive. Most of the ESBL-positive isolates were related to ICU and the least of them were related to neonatal ward. Conclusion: The present study indicates the high prevalence of ESBL producing Enterobacteriaceae family especially in inpatients. Limiting the spread of such superbugs is of utmost importance.